1985
DOI: 10.1177/000456328502200417
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Erythrocyte Transketolase Activity and the Thiamine Pyrophosphate Effect during Storage of Blood

Abstract: SUMMARY. Whole blood and washed erythrocytes from nutritionally normal and abnormal elderly patients were stored at room temperature, 4 c e and -20 c e for up to 14 days. In both groups, and under all storage conditions, the erythrocyte transketolase (ETK) activity and the thiamine pyrophosphate (TPP) effect decreased with time of storage. The ETK activity for specimens stored at -20 c e decreased significantly by day 14 (P<0·05). The TPP effect in specimens stored at -2OCe decreased significantly in the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Two laboratories had to be used for ETK determinations and haemoglobin concentrations were not assayed in Oxford and therefore basal EKTA could not be expressed for these samples. The long sample storage period is unlikely to have affected α [35], [36] and if it did, it would have tended to underestimate thiamin deficiency [42]. It is likely that infants with thiamin deficiency have other clinically important nutritional deficiencies, such as vitamin A, riboflavin and folate.…”
Section: Discussionmentioning
confidence: 99%
“…Two laboratories had to be used for ETK determinations and haemoglobin concentrations were not assayed in Oxford and therefore basal EKTA could not be expressed for these samples. The long sample storage period is unlikely to have affected α [35], [36] and if it did, it would have tended to underestimate thiamin deficiency [42]. It is likely that infants with thiamin deficiency have other clinically important nutritional deficiencies, such as vitamin A, riboflavin and folate.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 62,63 have identified potential problems with the performance and interpretation of this assay, including a gradual deterioration of samples during several months of storage at -20°C and a loss of reactivatable apoenzyme during chronic deficiency in vivo. 62 This necessitates the calculation and recording of basal enzyme activity per unit of haemoglobin or blood volume, as well as alpha or ETKAC,63 since a low basal activity can provide additional evidence of deficiency, in circumstances where the activation coefficient may prove either unreliable, or insufficiently discriminatory.…”
Section: Methodsmentioning
confidence: 99%
“…Stability data were gathered in response to information kindly supplied by Puxty et al, 11 principally concerning serious deterioration of ETKA and 'TPP Effects' during two weeks' storage of haemolysate at -20°C. Leunis et al have recently reported similar losses of activity.r" With -70°C refrigeration available, it seemed sensible to see if this temperature gave better results.…”
Section: Fluorimetric Measurement Of Etka 185mentioning
confidence: 99%